2018
DOI: 10.1038/s41598-018-35728-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of cysteine oxidative post-translational modifications in high and low aerobic capacity

Abstract: Given the association between high aerobic capacity and the prevention of metabolic diseases, elucidating the mechanisms by which high aerobic capacity regulates whole-body metabolic homeostasis is a major research challenge. Oxidative post-translational modifications (Ox-PTMs) of proteins can regulate cellular homeostasis in skeletal and cardiac muscles, but the relationship between Ox-PTMs and intrinsic components of oxidative energy metabolism is still unclear. Here, we evaluated the Ox-PTM profile in cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Our observation of increased content of three mitochondrial proteins in skeletal muscle therefore verified the increased physical activity in HCR rats. In contrast, the content of the same mitochondrial proteins in the heart was not increased in HCR rats compared to LCR rats, which is consistent with observations by Souza et al [ 56 ]. Interestingly, Souza et al observed only modest differences in mitochondrial respiratory rates which could suggest that the differences in sensitivity to IR injury between HCR and LCR rats is not due to variances in baseline myocardial mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation of increased content of three mitochondrial proteins in skeletal muscle therefore verified the increased physical activity in HCR rats. In contrast, the content of the same mitochondrial proteins in the heart was not increased in HCR rats compared to LCR rats, which is consistent with observations by Souza et al [ 56 ]. Interestingly, Souza et al observed only modest differences in mitochondrial respiratory rates which could suggest that the differences in sensitivity to IR injury between HCR and LCR rats is not due to variances in baseline myocardial mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
“…Muscle extracts were homogenized in degassed 2D buffer (7 M Urea, 2 M Thiourea, 2.5% CHAPS) without DTT (dithiothreitol) at pH 5.0. OxICAT and mass spectrometry were performed as previously described in detail 30 . Briefly, the ICAT reagent exists in an isotopically light 12 C‐form and heavy 13 C‐form.…”
Section: Methodsmentioning
confidence: 99%
“…Promising new biomarkers based on oxidative post-translational modifications of cardiac proteins have been reported by several independent research groups [109][110][111][112]. A direct relationship of oxidative modifications of proteins and cardiac function was shown in murine animal models [113]. Interestingly, while some reversible modifications of especially cysteine residues were found to be cardio-protective [114], oxidative damage in the form of irreversible modifications was detrimental for cardiac function in all cases and either related to HF [63] or decreased cardiac capacity [115].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Mitochondrial proteins operating in vicinity to the electron transport chain, a major contributor to cellular RNOS stress, are more likely to obtain oxPTMs. This is represented in the noticeable over-abundance of enzymes involved in the tricarboxyclic acid cycle such as malate dehydrogenase [113,119,120]. In enzymes harboring transition metals even intramolecular RNOS concentration differences can be observed as specific amino acids preferentially undergo oxidative modifications [72].…”
Section: Summary and Discussionmentioning
confidence: 99%